Digital Beamforming for Spaceborne Reflector-Based Synthetic Aperture Radar, Part 1: Basic imaging modes - Younis, Marwan; De Almeida, Felipe Queiroz; Villano, Michelangelo; Huber, Sigurd; Krieger, Gerhard; Moreira, Alberto (IEEE Geoscience and Remote Sensing Magazine, 2021)
Deployable reflector antennas illuminated by a digital feed array enable spaceborne synthetic aperture radar (SAR) systems to image an ultrawide, continuous swath at a fine azimuth resolution. This is facilitated by the use of dedicated imaging modes and by multidimensional digital beamforming (DBF) techniques. This article is part 1 of a tutorial trilogy, where a focus is put on the required onboard functionality, operational techniques, and DBF aspects, for which a rigorous mathematical description is included. To maintain general validity, the functional implementation for the various modes is detailed, thus avoiding restricting the description to a specific realization. The reader is assumed to be familiar with the general concept of SAR and, otherwise, referred to the literature on the topic. The approach followed in the trilogy is to start with a basic imaging concept and then move to more advanced modes, thus successively increasing the complexity; the mathematical description follows the same approach.
CRIS-Team WoS Importer:2021-10-08